Physiological and transcriptional characterization of Escherichia coli strains lacking interconversion of phosphoenolpyruvate and pyruvate when glucose and acetate are coutilized. Issue 6 (28th January 2014) - Sabido, Andrea; Sigala, Juan Carlos; Hernández‐Chávez, Georgina; Flores, Noemí; Gosset, Guillermo; Bolívar, Francisco
ABSTRACT Phosphoenolpyruvate (PEP) is a precursor involved in the biosynthesis of aromatics and other valuable compounds in Escherichia coli. The PEP:carbohydrate phosphotransferase system (PTS) is the major glucose transport system and the largest PEP consumer. To increase intracellular PEP availability for aromatics production purposes, mutant strains of E. coli JM101 devoid of the ptsHIcrr operon (PB11 strain) have been previously generated. In this derivative, transport and growth rate on glucose decreased significantly. A laboratory evolved strain derived from PB11 that partially recovered its growth capacity on glucose was named PB12. In the present study, we blocked carbon skeletons interchange between PEP and pyruvate (PYR) in these ptsHIcrr− strains by deleting the pykA, pykF, and ppsA genes. The PB11 pykAF−ppsA− strain exhibited no growth on glucose or acetate alone, but it was viable when both substrates were consumed simultaneously. In contrast, the PB12 pykAF−ppsA− strain displayed a low growth rate on glucose or acetate alone, but in the mixture, growth was significantly improved. RT‐qPCR expression analysis of PB11 pykAF−ppsA− growing with both carbon sources showed a downregulation of all central metabolic pathways compared with its parental PB11 strain. Under the same conditions, transcription of most of the genes in PB12 pykAF−ppsA− did not change, and few like aceBAK, sfcA, and poxB were overexpressed compared with PB12. We explored the aromatics production capabilities of both ptsHIcrr−pykAF−ppsA− strains and the engineered PB12 pykAF−ppsA−tyrR−pheAev2+/pJLBaroGfbrtktA enhanced the yield of aromatic compounds when coutilizing glucose and acetate compared with the control strain PB12 tyrR−pheAev2+/pJLBaroGfbrtktA. Biotechnol. Bioeng. 2014;111: 1150–1160. © 2013 The Authors. Biotechnology and Bioengineering Published by Wiley Periodicals, Inc.